Vibrational and Normal Coordinate Analysis of 1-Methyl-2,6-diphenylpiperidone - Chithambarathanu, T.; Umayorubhagan, V.; Krishnakumar, V. (Asian Journal of Chemistry, 2010)
Normal coordinate analysis of the fundamental vibrations of the title compound has been carried out by assuming C2v point group symmetry. The observed FTIR vibrations have been interpreted and assigned based on the normal coordinate analysis. The potential energy distribution analysis also confirms the present assignments.